ISLAMIC SECTS AND PARTIES DEVELOPING, USED TO DEVELOP AND NON-DEVELOPING ACTIVITY IN THE REPUBLIC OF BULGARIA: ISLAMIC SECTS AND PARTIES DEVELOPING, USED TO DEVELOP AND NON-DEVELOPING ACTIVITY IN THE REPUBLIC OF BULGARIA - Hristov, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Attempts and processes have been observed to disseminate radical Islamic ideas among the Muslim population under the cover of missionary activities of various Muslim organizations. In connection with the above, the report explores the existing Islamic sects and parties on the territory of the Republic of Bulgaria.